Transforming individuals and institutions through competency-based faculty development - Robertson, Mariah L.; Cofrancesco Jr, Joseph; Levine, Rachel B. (Frontiers in Medicine, 2025)
Faculty development (FD) is foundational to advancing the quality of health professions education and, by extension, the healthcare system. While FD has traditionally emphasized teaching, its scope now includes educational leadership, scholarship, and systems-level change. This Perspective argues for the adoption of competency-based FD frameworks to not only support individual educator growth but also catalyze institutional transformation. Aligning FD programming with established educator competencies fosters professional identity, enables targeted skill development, and legitimizes educational contributions in academic medicine. Drawing from global models—including frameworks from the United States, United Kingdom, the Netherlands, and Lebanon—we illustrate how institutions can adapt existing structures to their specific needs. We describe our experience at Johns Hopkins School of Medicine, where a locally tailored competency framework was developed to define six core educator domains and associated metrics. This initiative has driven significant changes in FD offerings, educator recognition, and promotion processes. Key lessons include the importance of making educator work visible, aligning FD with promotion pathways, delivering flexible programming, and engaging stakeholders early. Adapting frameworks to local contexts clarifies institutional values, supports customized faculty programming, and strengthens advocacy for educational excellence. Ultimately, competency-based FD serves as a strategic tool to enhance faculty satisfaction, retention, and institutional impact. We encourage institutions to adopt a systems-oriented approach that integrates shared standards with local relevance to elevate educational practice and culture.